Niger : Staff Report for the 2001 Article IV Consultation, the Second Review and Second Annual Program Under the Poverty Reduction and Growth Facility Arrangement, and Request for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2002)
This paper evaluates Niger's 2001 Article IV Consultation, the Second Review and Second Annual Program Under the Poverty Reduction and Growth Facility (PRGF) Arrangement, and a Request for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). The corrective measures taken by the authorities since June 2001 have been successful in bringing the program back on track. All end-September 2001 quantitative performance criteria and benchmarks were met, except for a small and temporary accumulation of external payments arrears, for which the authorities are requesting a waiver.